Memanfaatkan Sampah Plastik Menggunakan Metode Ecobrick sebagai Solusi untuk Mengurangi Limbah Plastik - Matsuri, Matsuri; Widianto Atmojo, Idam Ragil; Chumdari, Chumdari; Adi, Fadhil Purnama; Ardiansyah, Roy; Saputri, Dwi Yuniasih (FKIP Universitas Sebelas Maret, 2024)
Plastic waste is a serious problem in Indonesia because plastic cannot be decomposed naturally and can have a negative impact on the environment and public health. Then the 3R principle is applied, namely Reduce, Reuse, and Recycle. This socialization activity will focus on the principle of Recycle (recycling) through ecobrick in the village of Shoulder RT 04 RW 07 Jati, Jaten District, Karanganyar Regency. Ecobrick itself is a creative effort to manage plastic waste into useful objects that have use value and sale value, reducing pollution and toxins caused by plastic waste. Making ecobrick does not require special skills and only requires a lot of money because it uses household waste plastic as the main material. The purpose of holding the socialization in Pundak Village RT 04 RW 07, Jati, Jaten District, Karanganyar Regency is to overcome plastic waste and provide an understanding of how to recycle plastic waste using the ecobrick method. The methods used in this ecobrick socialization are questionnaires, lectures, and demonstrations. The result of this socialization is a decrease in the amount of untreated plastic waste which is related to the greater awareness of residents in the Village of Pundak RT 04 RW 07, Jati, Jaten District, Karanganyar Regency in waste management.